2017
DOI: 10.1248/cpb.c16-00949
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of (<i>R</i>)-Terbutaline for Recyclable Catalytic Asymmetric Transfer Hydrogenation in Ionic Liquids

Abstract: We synthesize optically active (R)-terbutaline 2, which is an anti-asthmatic drug, through recyclable catalytic asymmetric transfer hydrogenation (RCATH). Various chloroketones 4 were prepared and RCATH was performed on them. The products exhibit moderate to high enantioselectivity. In particular, the hydrogenation of acyl substituted substrates 4c yields chiral secondary alcohols 5c in good yield and enantioselectivity. Furthermore, (R)-terbutaline 2 can be synthesized in one step from the resulting secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[6][7][8][9][10][11] Recently, Zhuo Fan et al reported that, S-enantiomer of TBT may activate muscarinic receptors which could generate the airway hyperreactivity of racemic terbutaline. 12 To date, much efforts have been devoted to produce R-TBT 5, either by absolute asymmetric synthesis, 13 or by chemo-enzymatic method in which asymmetric reduction of a substituted α-chloroacetophenone derivative with cultured wholecell biocatalyst of yeast (Williopsis californica JCM 3600), 14 or by catalytic asymmetric synthesis from chloroketones, 15 or using chiral selector (β-cyclodextrin or its derivatives). [16][17][18][19] However, these methods couldn't achieve products with high optical purity for industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Recently, Zhuo Fan et al reported that, S-enantiomer of TBT may activate muscarinic receptors which could generate the airway hyperreactivity of racemic terbutaline. 12 To date, much efforts have been devoted to produce R-TBT 5, either by absolute asymmetric synthesis, 13 or by chemo-enzymatic method in which asymmetric reduction of a substituted α-chloroacetophenone derivative with cultured wholecell biocatalyst of yeast (Williopsis californica JCM 3600), 14 or by catalytic asymmetric synthesis from chloroketones, 15 or using chiral selector (β-cyclodextrin or its derivatives). [16][17][18][19] However, these methods couldn't achieve products with high optical purity for industrial application.…”
Section: Introductionmentioning
confidence: 99%